2019
DOI: 10.1002/pbc.27767
|View full text |Cite
|
Sign up to set email alerts
|

“I wish someone had once asked me how I'm doing”: Disadvantages and support needs faced by parents of long‐term childhood cancer survivors

Abstract: Background Childhood cancer affects the whole family and can have a lasting impact on parents of childhood cancer survivors (CCS). We aimed to (1) describe parents’ perspective of currently experienced disadvantages and of their support needs during treatment, after treatment, and today; (2) identify characteristics associated with disadvantages and support needs; and (3) describe the use of existing support services. Procedure In this population‐based study, we identified parents of CCS (diagnosed ≤16 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…Furthermore, future studies could also explore the experiences of children with cancer, including their fathers and siblings to understand their psychosocial needs. Third, similar to other studies, 17,19 this study explored the retrospective parental experience of having a child with cancer, which may be different from prospective experiences, and thus may contain some level of recall bias. Nevertheless, the existing literature suggests that both prospective 11,21 and retrospective studies 17,19 on parental experiences revealed consistent findings that significant parental emotional distress was reported, especially in the early stages of receiving the child' s cancer diagnosis.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Furthermore, future studies could also explore the experiences of children with cancer, including their fathers and siblings to understand their psychosocial needs. Third, similar to other studies, 17,19 this study explored the retrospective parental experience of having a child with cancer, which may be different from prospective experiences, and thus may contain some level of recall bias. Nevertheless, the existing literature suggests that both prospective 11,21 and retrospective studies 17,19 on parental experiences revealed consistent findings that significant parental emotional distress was reported, especially in the early stages of receiving the child' s cancer diagnosis.…”
Section: Discussionmentioning
confidence: 95%
“…11 Such findings are also consistent with international studies. 6,19 Although further research is required, the current finding that Singaporean parents are receptive towards receiving emotional support from healthcare professionals is encouraging. The findings indicated a need for an early and holistic parental support programme to address intrapersonal, interpersonal and financial needs.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations